Multinationals need closer ties as globalization retreats - Huy, Quy Nguyen; Moschieri, Caterina; Ravasi, Davide 1970- (MIT Sloan Management Review, 2022)
Researchers studied eight multinational firms to learn what makes some companies better able to deal with a host country's hostility than others. They found that firms operating in foreign countries through a joint venture with local companies tended to rely too much on their partners to relate to stakeholders and missed early warning signs of hostile government actions. In comparison, companies that operated through directly controlled subsidiaries had better intelligence and better outcomes.
"Reprint 64115."
Keywords: International business enterprises; Entreprises multinationales